Integrated Care of Modifiable Risk Factors in Patients with Ischemic Stroke can Improve the Reproductivity of State (Medical Forum Monthly, 2024)
Objectives: To identify modifiable risk factors in patient with ischemic stroke in tertiary care hospital of Karachi.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted in Medical Unit-I, II, III, Abbasi Shaheed Hospital Karachi from 21st September 2006 – 21st March 2007.Material and method: All patients admitted during six months period, who met the inclusion criteria of recent ischemic stroke, were analyzed according to questionnaire for six selected variable i.e hypertension, diabetes mellitus, cigarette smoking, obesity, hyperlipidemia and cardiac disorder.Results: Average age of patient was 65. 57 years. Hypertension involved in 76.6%, diabetes mellitus 53%, cigarette smoking in 31.7%, 13.3% patients were obese , hyperlipimedia found in 48.3% patients and cardiac disorder in 5%patients.Combination of hypertension and smoking was found in 38.46%, combination of hypertension, diabetes and hyperlipidemia in 44.23% and combination of diabetes, obesity and hyperlipidemia in 17.31% patients.Conclusion: Among the six risk factors analyzed, data revealed a significant effect of hypertension. Other contributing risk factors in order of frequency were diabetes, hyperlipidemia, smoking, obesity and cardiac disorders. Combinations of risk factors i.e hypertension and smoking, or combination of hypertension, diabetes and hyperlipidemia, or combination of diabetes, obesity and hyperlipidemia were the commonly occurring co-morbidities in patients presented with ischemic stroke.